Coherent Judaism : constructive theology, creation, & halakhah - Cherry, Shai (Academic Studies Press, 2020)
"Coherent Judaism begins by excavating the theologies within the Torah and tracing their careers through the Jewish Enlightenment of the eighteenth century. Any compelling, contemporary Judaism must cohere as much as possible with traditional Judaism and everything else we believe to be true about our world. The challenge is that over the past two centuries, our understandings of both the Torah and nature have radically changed. Nevertheless, much Jewish wisdom can be translated into a contemporary idiom that both coheres with all that we believe and enriches our lives as individuals and within our communities. Coherent Judaism explains why pre-modern Judaism opted to privilege consensus around Jewish behavior (halakhah) over belief. The stresses of modernity have conspired to reveal the incoherence of that traditional approach. In our post-Darwinian and post-Holocaust world, theology must be able to withstand the challenges of science and history. Traditional Jewish theologies have the resources to meet those challenges. Coherent Judaism concludes by presenting a philosophy of halakhah that is faithful to the covenantal aspiration to live long on the land that the Lord, our God, has given us"--